Development Student Worksheet Based on Problem-Based Learning (PBL) on Matrix Materials for Class XI - Tutut Siswati; Sri Rezeki; Aulia Sthephani; Lilis Marina Angraini (AlphaMath : Journal of Mathematics Education, 2021)
This study aims to determine the validity of PBL-based worksheets on the XI class matrix material. The type of research used is the research and development method (R & D). This research stage will be based on the ADDIE development stage which consists of the analysis, design, and development stages. The instrument used in this research is the LKPD validation sheet, and the data obtained will be processed descriptively. From the research results, it is known that the results of the LKPD validation are 87.92% with a very valid category. Based on the final results of this study, the Problem Based Learning (PBL) Worksheet on Class XI Matrix Material is very valid.